(untitled) (Canadian Dermatology Today, 2023)
As a visible organ, the skin reveals powerful information about both internal and external health. Canada is the world’s second largest country landmass, and approximately 60% of Canadian Indigenous peoples reside in Northern and/or Rural Communities (NRCIC), which are generally underserviced. Barriers such as lack of health care access lead to skin health disparities, which are evident in the literature documenting high burdens of bacterial skin and soft tissue infections (SSTIs) in NRCIC across Canada, mainly caused by Staphylococcus aureus (including methicillin-resistant Staphylococcus aureus [MRSA]) and Streptococcus. A review of national and regional data published over the last 15 years is included, followed by narrative synthesis of evidence-based solutions.